Seismic evaluation of buildings with post-tensioned floors by pushover analysis - Shah, B. A.; Mistry, D. A.; Patodi, S. C. (Journal of Structural Engineering, 2024)
The present study compares the seismic performance of a typical RC framed structure of an overall plan dimension of 16m x 16m having panel size of 8m x 8m with the following three variations in its frame modeling. The first model consists of a conventional RC frame with all beams and columns as RCC. The second model considers peripheral beams as RCC and interior beams with PT (Post Tensioned) tendons. The third model consists of all beams having PT tendons. The models studied are varied in height from Ground + three stories to Ground + seven stories with square shaped cross section of columns. The column height is considered as 3.5m for each floor. Static Nonlinear Pushover analysis is carried out for all the fifteen models generated using SAP2000 software. Seismic performance of G+3 to G+7 storey frames with peripheral RC beams and internal PT beams is found to be the best, followed by frames with all RC beams. Performance of frames with all PT beams is slightly below that with all RC beams. However, it has been observed that the performance of frames with all PT beams is also quite good even without any separate lateral force resisting system.